2001
DOI: 10.1080/00140130110068933
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of rectal temperature from ear canal temperature

Abstract: Personal heat strain monitoring provides the best means for maximizing worker safety and productivity in hot jobs. The present study compared methods for reducing the environmental effect on aural canal temperature in an attempt to reduce the predictive error of a personal heat stress monitor (QST) and a simple ear thermistor (EAR). Subjects underwent three exposures in impermeable protective clothing (PC) in an environment of 30.1 degrees C wet bulb globe temperature (WBGT) wearing either ear plugs (PLG), ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…The only article evaluating the use of auditory canal temperatures in actual workplace settings concludes that the method was a poor index of core temperature; however, that report failed to report the precise positioning of the thermocouple 10) . Muir et al used infrared sensors to measure auditory canal temperatures and observed differences from rectal temperatures exceeding 0.6°C, but failed to verify the location of the sensor 4) . Some studies have placed the thermocouple within a few millimeters of the tympanic membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The only article evaluating the use of auditory canal temperatures in actual workplace settings concludes that the method was a poor index of core temperature; however, that report failed to report the precise positioning of the thermocouple 10) . Muir et al used infrared sensors to measure auditory canal temperatures and observed differences from rectal temperatures exceeding 0.6°C, but failed to verify the location of the sensor 4) . Some studies have placed the thermocouple within a few millimeters of the tympanic membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the accuracy of measurements may rely on the improvement of signal/data acquisition and device stability, potentially through the implementation of new materials, as exemplified by graphene-coated T sensors (Chaglla et al, 2018 ). Probe development for T measurement should pursue personalization to adapt the device to the specific anatomy of each user (Muir et al, 2001 ; Venema et al, 2012 ; Ota et al, 2017 ), allowing a better insulation from external conditions (Teunissen et al, 2011 ; Strapazzon et al, 2015 ). For PPG-based measurements, accuracy may be improved by optimizing sensor design and wavelength [e.g., optimal LED-photodiode distance, shunt-light reduction (Buschmann and Huang, 2010 )], but also by developing suitable signal processing and advanced algorithms for noise removal (Poh et al, 2010 ; Poh and Kittler, 2012 ; Tomita et al, 2018 ).…”
Section: Limitations and Future Developmentsmentioning
confidence: 99%
“…Alternatively, insulating the auditory canal from the environment is likely to limit the temperature gradient drastically within the auditory canal, 29 permitting improved measurement accuracy through use of a tympanic probe. 30 While Pryor et al 26 reported that tympanic probes were more erroneous than infrared tympanic monitors, the precise location of the probe was not detailed and the auditory canal was not insulated in that study.…”
Section: Discussionmentioning
confidence: 99%